Evaluate the use of Mehlich-III compared to Mehlich-I as a soil test in Northeast Florida - Amanpreet Kaur Sandhu; Ayush Sharma; Navdeep Kaur; Lincoln Zotarelli; Kelly Morgan; Lakesh K. Sharma (Farming System)
Soil laboratories throughout the United States have widely integrated the Mehlich-III (M-III), derived from Mehlich-I (M-I), methodologies to extract soil nutrients. However, there have been concerns regarding its precision. The University of Florida's Hastings Agricultural and Extension Center (HAEC) conducted a soil sampling during the spring of 2021. This research aimed to rigorously compare the extraction efficiencies of M-I and M-III, specifically focusing on critical soil nutrients like phosphorus (P), potassium (K), magnesium (Mg), calcium (Ca), boron (B), copper (Cu), iron (Fe), manganese (Mn), and zinc (Zn). From forty-six meticulously chosen fields, 276 composite soil samples derived from two distinct depth strata (0–15 ​cm and 15–50 ​cm) were analyzed using both methods. Our findings highlighted the superior extraction prowess of M-III, which showcased an efficiency almost threefold compared to M-I. Intriguingly, the correlation between M-I and M-III extraction efficiencies weakened with escalating soil nutrient concentrations. The coefficient of determination (r2) between M-I and M-III had a high correlation value and was statistically significant (p<0.05) for all macro- and micronutrients. We found that the correlation between M-I and M-III became more robust with an increase in sample size and a higher correlation coefficient. It is noteworthy to mention that the M-III method has the propensity to provide slightly inflated soil nutrient estimations. Since soil labs worldwide use M-III equations derived from M-I, this study proposes that soil labs reinvestigate and possibly adopt new correlation equations to estimate soil nutrients using M-III.